(untitled) (Third Sector Social Economic Review, 2021)
The Covid-19 pandemic, which was declared a pandemic by the World Health Organization in March 2020, has affected all sectors a positive or negative way. The banking sector has been one of the sectors most affected by the pandemic due to the fact that it is a sector where face-to-face communication is intense and it is one of the basic dynamics of economies. In this process, various practices such as postponing loan payments, restructuring loans and low-interest loan campaigns were implemented under the leadership of state-owned deposit banks in Turkey. In this study, the development of the profitability levels of state-owned deposit banks, domestic deposit banks, foreign deposit banks and participation banks operating in the Turkish banking sector in the one-year period before the pandemic and the one-year period during the pandemic period were analyzed. As a result of the study, it was found that the interest expenses and other expenses other than interest of state-owned deposit banks increased compared to other types of banks; On the other hand, it was observed that the net profit levels, return on assets, return on equity ratios and net interest margins decreased.